Democratic dilemmas of teaching service-learning : curricular strategies for success - Cress, Christine M. (Christine Marie), 1962-; Donahue, David M. (Stylus Pub., 2011)
Recognizing that teaching, in general, and service- learning, in particular, are inherently political, this book faces up to the resulting predicaments that inevitably arise in the classroom. By framing them as a vital and productive part of the process of teaching and learning for political engagement, this book offers the reader new ways to think about and address seemingly intractable ideological issues. Using real incidents, the contributors explore the democratic intersections of various political beliefs along with race/ethnicity, class, gender, ability, sexual orientation, and other con.